The Implementation of Prepopulated Value Added Tax-In on E-Invoice 3.0 at Crediting of Value Added Tax-In at PT. XYZ - Didi Adi Supriadi; Nurma Risa; Mundianah; Syahfebriano Bogar (Future Science, 2022)
This study aims to determine the implementation of prepopulated value added tax/VAT-in on e-invoice 3.0 on crediting input of VAT-in at PT XYZ and besides that this study also aims to determine the effectiveness of using prepopulated input vat-in on e-invoice 3.0 at PT.XYZ. The conclusions from the researches of the implementation of the prepopulated menu. The object of this research is PT XYZ, a company engaged in the field of expedition by carrying out and completing works such as land preparation, cut & fill, infrastructure, red soil warehouses and road construction. The research data used in this study is secondary data. In meeting the needs of secondary data, researchers collected data by interviews, summation and observation. The results of this study indicate that the prepopulated implementation menu at PT XYZ is less effective.